في تـرقيــة مهارة الطلاب على الحـــوار بــالمدرسة الثـــانويــة الحكومــية 2 ســغلي Discovery Based Learning فــعــالـــية تـــطبيق أسلــوب - Tsabirin, Muhammad (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2021)
Conversation is one aspect of speaking ability and it is also one aspect of language competence. As an art of language, this cannot be achieved without practices so they can speak fluently and be understood by others. MAN 2 Sigli is one of schools located in Meureudu which puts much attention on teaching and learning Arabic, and also the students use Arabic inside and outside the school. However, the students speak less Arabic eventhough they have a lot of Arabic vocabularies. However, based on preliminary study conducted at MAN 2 Sigli. The techers still use traditional method in teaching resulting in the students difficulty in speaking. Those to overcome that problem, the researcher would like to implement discovery based learning in teaching and lerning speaking. Discovery based learning model is one 2013 curriculum and it focuses more on the use of various materials and students activities to obtain information from internet, book, magazine, etc. The aims of this study are to find out the students learning interst in using Discovery Based Learning, and to investigate the effectiveness of Discovery Based Learning in increasing the student ability in understanding conversation at MAN 2 Sigli. The research design used in this study are quantity and quantitative method based on true experimental research design. The researcher used direct observation and test as research instrument in collecting the data needed. The result of this study shows that: 1) The use of Discovery Based Learning increased the students interest is learning conversation. 2) Discovery Based Learning is effective in increasing the students speaking ability.